IMPROVEMENT OF TECHNICAL-TACTICAL, SENSORIMOTOR AND THINKING PROCESSES OF HIGHLY SKILLED BOXERS - Abdullayev F. T. (European Science Publishing, 2024)
During technical and tactical training, highly qualified boxers are trained to improve their individual combat style, strengthen technical tools and tactical movements, develop special thinking and sensorimotor skills (time, distance, impact, anticipatory reaction, concentration, distribution and transfer, decision-making speed and coherence) a personalized training and exercise plan was created to ensure balanced development. The structure of the trainer's actions during individual training with flat gloves has been systematized.
Keywords: Boxer, technical and tactical training, sensorimotor, trainer, flat gloves, competition, training fights, strikes.